The Juan Sebastián Elcano School Ship on the shores of Japan: Transnational diplomacy in 1935 - Alonso Verdugo, Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
By the mid-1930s, relations between Spain and Japan had gone from cordial to distant as a result of the position that Spain had adopted in the League of Nations regarding the Japanese occupation of Manchuria. In this climate of tensions, some attempts would arise to recover the state of those relations, and a good example of that desire for improvement was the visit of the Juan Sebastián Elcano School Ship to Japan in January 1935 and the treatment it would receive both upon its arrival as during the seven days it remained in Japanese waters.